Metoda Sederhana untuk Memperbaiki Kinerja Motor Listrik 3 Fasa berdasarkan Insulation Resistance Test - Ruri Irwanto, Asep Ahmad; Hermawan, H (Jurnal Pengelolaan Laboratorium Pendidikan, 2024)
In the electrical energy conversion laboratory, the stable operation of the induction motor is one of the most important factors. Failure of induction motor operation can be fatal in research activities in energy conversion laboratories. Prevention is needed so that the performance of induction motors remains optimal. this paper was created as an alternative for laboratory users of electrical energy conversion in maintaining the performance of induction motors. Based on a survey conducted by the Institute of Electrical and Electronics Engineers (IEEE), the main cause of electric motor operation failure is generally caused by insulation failure, so electric motor testing is generally dominated by insulation testing. Many insulation testing methods such as Insulation Resistance (IR) testing, Polarization Index (PI), Delta tangent, and other tests. In this paper, IR-based testing is proposed, because it is relatively cheap and easy to implement. The IR testing process is carried out using direct voltage from the Insulation Tester to the sample to be tested using the IEEE 43TM-2013 Standard. The test results show the IR value of the sample motor is good. This condition is categorized as safe to operate, so research activities that use induction motors can run well and safely.